Determination of the amount of leg length inequality that alters spinal posture in healthy subjects using rasterstereography - Rapp, Walter; Przibylla, Anna; Jungbluth, Pascal; Hakimi, Mohssen; Schneppendahl, Johannes; Thelen, Simon; Wild, Michael; Betsch, Marcel (European Spine Journal, 2013)
Purpose: Leg length inequalities (LLIs) can result in an increased energy consumption, abnormal gait or osteoarthritis of the hip. In a previous study we simulated different LLIs of up to 15 mm and evaluated their effects on the pelvic position and spinal posture. We found a correlation between LLIs and resulting changes of the pelvic position. Despite suggestions in the literature we were not able to detect significant changes of the spinal posture. Therefore, the purpose of this study was to determine the amount of LLI that would in fact alter the spinal posture. Methods: The subjects were placed on a simulation platform, whose height could be precisely controlled by the measuring device, to simulate different LLIs of up to 20 mm. For LLIs >20 mm, additional precision-cut wooden blocks were used under one foot. After an adaptation period the resulting changes of the pelvis and spine were measured with a rasterstereographic device. Results: We found a significant correlation between platform height changes and changes of the pelvic position. The frontal spinal parameters surface rotation and lateral deviation changed significantly when simulating differences greater than 20 mm. No changes of the sagittal spinal curvature were measured, however, a trend to decreasing kyphotic angles was noted. Conclusions: Our study has shown for the first time that LLIs >20 mm will lead to significant changes in the spinal posture of healthy test subjects. However, these changes were only found in frontal (surface rotation and lateral flexion) spinal parameters, but not in sagittal parameters. Here for the kyphotic angle only a tendency to decreasing angles was noted. We have also found a significant correlation between different leg lengths and changes of the pelvic position. Further, females and males seem to react in the same way to LLIs. © 2013 Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2022-07-20
Keywords: Functional scoliosis; Leg length inequalities; Pelvic obliquity; Posture; Rasterstereography